KESIAPAN ARSIPARIS MENGGUNAKAN E-ARSIP DALAM TATA KELOLA KEARSIPAN FAKULTAS TARBIYAH DAN KEGURUAN UIN RADEN INTAN LAMPUNG - Octaviona, Era; Kesuma, Mezan; Basyori, Ahmad (Jurnal El-Pustaka, 2020)
This research discusses the factors of the archival readiness and describes the e-archive system tailor-fit by the faculty of Tarbiyah and Teaching Science (FTK) UIN Raden Intan Lampung. The goal is to know the notes in opening historical records of the past, that is learned today, and become future learning. Also as securing archives: 1) either from damage or loss (safe); 2) The archive is easily rediscovered. The research is a qualitative description of the researches using data collection methods through observation, interviews, and documentation. The results of this study are: 1) can advance the effectiveness of the management of archives to implement an e-archive system, namely, the example is using Microsoft Acces, and 2) This E-archive has computer-based archival management and has the database system that can be accessed any time. Therefore, the important thing about the competent role of Archivists is qualified in the field. In addition, the archival and team are able to cooperate in archives management and are committed to developing the management of the archives maximumly.